UMPSA and NXU celebrate a decade of strategic synergy - Naqiah, Puaad (UMPSA, 2025)
KUALA LUMPUR, 3 June 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and Ningxia University (NXU), China, celebrated a meaningful decade of academic collaboration with the 10th UMPSA-NXU Strategic Synergy Dinner held at Irama Dining, Kuala Lumpur.